Client profitability of diffusion segments across countries for multi-generational innovations: The influence of firm, market, and cross-national differences. Issue 9 (December 2018) - Sood, Ashish; Kumar, V
Abstract There is scant research on the important managerial question of how to maximize returns on investments in either international business or international marketing literature. We propose and test a conceptual framework using data from a large technology manufacturer-service provider. Despite early adoption by innovators and early adopters, the early majority segment is most profitable. However, the late majority segment and the early adopters segment are the next most profitable in the developed and emerging countries, respectively. We propose a decision support framework incorporating cross-national distances on single-generation and multi-generation profitability for MNEs offering multi-generational products in multinational markets to be more profitable. Résumé Dans la littérature eninternational business ou en marketing international, il y a peu de recherche sur l'importante question managériale de savoir comment maximiser les retours sur investissement. Nous proposons et testons un cadre conceptuel en utilisant les données d'un grand fabricant-fournisseur de services de technologies. Malgré l'adoption rapide par les innovateurs et les utilisateurs précoces, le segment majoritaire précoce est le plus rentable. Cependant, le segment majoritaire tardif et le segment des utilisateurs précoces sont ensuite les plus rentables, respectivement dans les pays développés et émergents. Nous proposons un cadre d'aide à la décision intégrant les distances transnationales concernant la rentabilité d'une génération et de multiples générations pour les entreprises multinationales offrant des produits multigénérationnels sur les marchés multinationaux pour être plus rentables. Resumen Hay escasa investigación sobre la importante pregunta gerencial de cómo maximizar el rendimiento de las inversiones ya sea en la literatura de negocios internacionales o de marketing internacional. Proponemos y probamos un marco conceptual utilizando datos de un proveedor de servicios de manufactura de grandes tecnologías. A pesar de la adopción temprana por parte de los innovadores y los primeros en adoptar, el segmento de mayoría que lo hace más temprano es el más rentable. Sin embargo, el segmento de la mayoría que lo hace después y el segmento de los primeros adoptantes son los siguientes en rentabilidad en países desarrollados y emergentes, respectivamente. Proponemos un marco de apoyo a la decisión que incorpore distancias transnacionales en la rentabilidad en una generación individual, y multi-generacional para que las EMN que ofrecen productos multi-generacionales en los mercados multinacionales sean más rentables. Resumo Há escassa pesquisa sobre a importante questão gerencial de como maximizar retornos sobre investimentos tanto na literatura de negócios internacionais quanto na de marketing internacional. Propomos e testamos um modelo conceitual usando dados de um fornecedor de serviços de uma grande fabricante da área de tecnologia. Apesar da adoção antecipada por inovadores e pioneiros, o segmento de maioria precoce é mais lucrativo. No entanto, o segmento de maioria tardia e o segmento de pioneiros representam o segundo grupo mais lucrativo nos países desenvolvidos e emergentes, respectivamente. Propomos um modelo de apoio à decisão incorporando distâncias transnacionais na rentabilidade de geração única e geração múltipla para que as MNEs que oferecem produtos multigeracionais em mercados multinacionais sejam mais lucrativas. 摘要 关于如何最大限度地提高投资回报这个重要的管理问题在国际商务或国际营销文献里研究甚少。我们用来自大型技术制造-服务商的数据提出并测试了一个理论框架。尽管被创新者和早期采用者所采纳, 早期占多数的细分区是最有利可图的。然而, 后期占多数的细分区和早期采用者细分区分别都是发达国家和新兴国家下一个最有利可图的细分区。我们提出了一个决策支持框架, 容纳对单代和多代利润率的跨国距离, 为跨国公司在跨国市场提供更多利润的多代产品。.